Research on the Impact of Digital Inclusive Finance on Guangxi’s Economic Growth - Yiren Feng; Dongsheng Liao; Yaqi Liu; Han Li; Jinlu Huang (Journal of Frontier in Economic and Management Research, 2025)
The digital inclusive financial system digitizes and informationizes the inclusive financial service system, breaks through the physical limitations, expands the service scope of traditional financial services, and uses Internet technology to promote the development of financial services in underdeveloped areas and the sound operation of the financial system.Therefore, it is very forward-looking to study the relationship between digital inclusive finance and economic growth, and make suggestions on the development of digital inclusive finance in Guangxi. Based on this, this paper selects the data of 14 prefecture level cities in Guangxi from 2011 to 2020, and on the basis of theoretical analysis to put forward assumptions, conducts empirical analysis on the impact of digital inclusive finance on economic growth to verify relevant assumptions. The research results show that digital inclusive finance can effectively promote the economic development of Guangxi, while promoting economic growth through two paths, namely, improving the living standards of rural residents and promoting the optimization and upgrading of industrial structure.Based on the research results, we further put forward policy recommendations such as improving the local digital inclusive financial product system, improving rural financial coverage, giving play to government guidance, and improving the relevant legal system.